Secret sauce : 200 copycat recipes to re-create your favorite restaurant sauces, dips, and dressings - Jaggers, Kelly (Adams Media, an imprint of Simon & Schuster, LLC, 2025)
"Enjoy your favorite restaurant sauces... without waiting in lines, paying inflated prices, or stocking up on sauce packets to save for later meals. With 200 quick and simple recipes, you can now recreate your favorite restaurant sauces, dressings, and dips right at home. You'll find iconic recipes like: Chipotle's Guacamole; McDonald's Tartar Sauce; Applebee's Oriental Vinaigrette; Shake Shack's Cheese Sauce; Carrabba's Dipping Oil; Taco Bell's Creamy Jalapeño Sauce; And more! With these classic, tried and true recipes, Secret Sauce helps you recreate popular restaurant sauces as closely as possible -- while still receiving the same rave reviews as the real thing -- on a much smaller tab." --